Economics Analysis of Legal Approach In the Progression of West Lampung Traditional Cultural Expression - Jainah, Zainab Ompu; B, Erlina; Safitri, Melisa; Seftiniara, Intan Nurina; Rusli, Tami (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The value of West Lampung's traditional cultural expressions has not been maximized for the local inhabitants. This article will explain how to implement the local government-requested preservation of West Lampung traditional expressions and their use in accordance with the Economic Analysis of Law framework. The results of the discussion indicate that the Protection and Utilization of Traditional Cultural Expressions has only reached the inventory stage, based on Law No. 28 of 2014 regarding Copyright, Law No. 5 of 2017 regarding Promotion of Culture, Law No. 11 of 2010 regarding Cultural Conservation and Regulations Government No. 6 of 2015 regarding Museums, and Regulation of the Minister of Culture No. 106 regarding Intangible Cultural Heritage of Indonesia. The Economic Analysis of Law demonstrates that West Lampung's traditional cultural expressions must be optimized in order to boost the region's income. This can be maximized through the collaboration of the local government with academics in the arts, artists, Youtubers, artists, and other parties who are already aware of what the global community desires as connoisseurs, so that professional processing can affect the welfare of the people of West Lampung